Kajian kecenderungan diare di Kota Manado tahun 2015-2017 - Lumintang, Joel; Ratag, Gustaaf A. E.; Ottay, Ronald I. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Background: Diarrhea is a disease with the main symptoms of increased dilution of stool / feces. Diarrhea can arise from a disorder that occurs in the intestinal tract. Diarrhea is the three most prominent diseases in North Sulawesi with the highest number of target discovery cases and the number of people with diarrhea in 2016 in Manado City.Aim: This research aimed to describe the tendency of diarrhea in the city of Manado. Method: This is a retrospective research with cross sectional design model and the data was taken from Health Profile Book of Manado City from 2015 - 2017.Result: Highest number of diarrhea per year is at Tuminting (2015), Kombos (2016), and Malalayang (2017) Health Centers andÂ  the fewest at Bailang Health Center (2015 and 2016), Paniki Bawah (2017). The highest average coverage of services three years in a row is at Tongkeina Health Center and the lowest at Bailang Health Center. Conclusion: The number of findings of diarrhea cases in the Health Center in Manado fromÂ  2015 to 2017 has decreased. The average health coverage services of diare in Health Center at Manado city has not yet reached the discovery target (100%)